Pengaruh Ukuran Perusahaan, Keputusan Pendanaan, dan Keputusan Investasi Terhadap Nilai Perusahaan Telekomunikasi di BEI Periode Tahun 2019-2023 (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of firm size, funding decisions, and investment decisions on firm value in telecommunication companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The dependent variable used is firm value, proxied by the Price to Book Value (PBV), while the independent variables consist of firm size (SIZE), funding decisions (Debt to Equity Ratio/DER), and investment decisions (Book Value of Asset/BVA). The analytical method employed is panel data regression using IBM SPSS Statistics. The results show that firm size and investment decisions have a positive and significant effect on firm value, while funding decisions have a negative and significant effect. Simultaneously, the three variables have a significant influence on firm value with a coefficient of determination (R²) of 0.659. These findings indicate that increasing assets and investments in infrastructure can enhance firm value, whereas excessive debt usage tends to reduce it.